Phonological Features of Assamese in Boro - Boro, Sanjay (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
The Assamese language belongs to the Indo- Aryan language family. It is the official language of the state of Assam along with two other co-official languages, i.e, Boro and Bengali. It is adopted as the common language among the communities that are used to speak different languages in the state of Assam. Boro is the major plain tribe of the state of Assam. The term Boro refers to both the language as well as the people that speak the language. They belong to the Tibeto-Burman branch of the Sino-Tibetan language family. The Boros are mostly bilingual. They use their mother tongue in every domain while speaking to the people of their community. The majority of the Boro speakers can speak Assamese fluently. They use Assamese as the contact language while communicating with people having different language mother tongues. As they come into contact with the Assamese speakers daily and frequently, they use the Assamese language, and as a result of it, many Assamese words are used in the Boro language with slight phonological changes. This paper discusses the phonological features of Assamese that are used in Boro.